Learn English Pronountation And Phonetic Transcription With Elsa Speaking Application : A Student Perception - Maulia Hafizhah; Larassati Dwi Wahyuni; Yani Lubis (Pusat riset dan Inovasi Nasional, 2023)
The aim of the study was to find out Student’s Perception about the Elsa speaking application was in teaching students how to pronounce words in English and providing phonetic transcriptions. It is qualitative research that collects results through the observations of researchers and questionnaires given to students. By providing the Elsa Speaking application with phonetic transcriptions that make it easy to learn English pronunciation and phonetics, with an exciting quiz view to make learning pronounces and phonetics fun, the Elsa Speaking application helps to learn transsyllabic phonics as well as practice the way it is spoken.